Immunomodulatory proteins from hookworms reduce cardiac inflammation and modulate regulatory responses in a mouse model of chronic Trypanosoma cruzi infection - Jones, Kathryn M.; Zhan, Bin; Ernste, Keenan J.; Villar, Maria Jose; Bisht, Nalini; Nguyen, Duc; Chang, Li-Yen; Poveda, Cristina; Robinson, Gonteria J.; Trivedi, Akshar J.; Hofferek, Colby J.; Decker, William K.; et al. (Frontiers in Parasitology, 2023)
Hookworms are parasitic helminths that secrete a variety of proteins that induce anti-inflammatory immune responses, stimulating increased CD4+Foxp3+ regulatory T cells and IL-10 production. Hookworm-derived recombinant proteins AIP-1 and AIP-2 have been shown to reduce inflammation in mouse models of inflammatory bowel disease and inflammatory airway disease by inducing CD4+Foxp3+ cells and IL-10 production. In contrast, chronic infection withthe protozoal parasite Trypanosoma cruzi, the causative agent of Chagas disease, leads to chronic inflammation in tissues. Persistence of the parasites in tissues drives chronic low-grade inflammation, with increased infiltration of inflammatory cells into the heart, accompanied by increased production of inflammatory cytokines. There are no current antiparasitic drugs that effectively reduce or prevent chronic myocarditis caused by the onset of Chagas disease, thus new therapies are urgently needed. Therefore, the impact of AIP-1 and AIP-2 on myocarditis was investigated in a mouse model of chronic T. cruzi infection. Female BALB/c mice infected with bioluminescent T. cruzi H1 strain trypomastigotes for 70 days were treated once daily for 7 days with 1mg/kg AIP-1 or AIP-2 protein by intraperitoneal injection. Control mice were left untreated or treated once daily for 14 days with 25mg/kg aspirin in drinking water. At 84 days of infection, splenocytes, cardiac tissue and serum were collected for evaluation. Treatment with both AIP-1 and AIP-2 proteins significantly reduced cardiac cellular infiltration, and reduced cardiac levels of IFNγ, IL-6 and IL-2. AIP-2 treatment reduced cardiac expression of COX-2. Further, while incubation with AIP-1 and AIP-2 proteins did not induce a significant upregulation of an immunoregulatory phenotype in dendritic cells (DC), there was a modest upregulation of CD11c+CD11b+MHCII+SIRPα+ expression, suggesting a regulatory phenotype. Ex-vivo stimulation of splenocytes from the treatment groups with AIP-1 loaded DC induced reduced levels of cytotoxic and pro-inflammatory T cells, stimulation with AIP-2 loaded DCs specifically induced enhanced levels of CD4+CD25+Foxp3+ regulatory T cells among treatment groups. All in vivo and in vitro results demonstrate that hookworm-derived AIP-1 and AIP-2 proteins reduce T. cruzi induced cardiac inflammation, possibly through multiple anti-inflammatory mechanisms.